Use of placebo controls in the evaluation of surgery: systematic review. - Wartolowska, K; Judge, A; Hopewell, S; Collins, G; Dean, B; Rombach, I; Brindley, D; Savulescu, J; Beard, D; Carr, A (BMJ Publishing Group, 2014)
OBJECTIVE: To investigate whether placebo controls should be used in the evaluation of surgical interventions. DESIGN: Systematic review. DATA SOURCES: We searched Medline, Embase, and the Cochrane Controlled Trials Register from their inception to November 2013. STUDY SELECTION: Randomised clinical trials comparing any surgical intervention with placebo. Surgery was defined as any procedure that both changes the anatomy and requires a skin incision or use of endoscopic techniques. DATA EXTRACTION: Three reviewers (KW, BJFD, IR) independently identified the relevant trials and extracted data on study details, outcomes, and harms from included studies. RESULTS: In 39 out of 53 (74%) trials there was improvement in the placebo arm and in 27 (51%) trials the effect of placebo did not differ from that of surgery. In 26 (49%) trials, surgery was superior to placebo but the magnitude of the effect of the surgical intervention over that of the placebo was generally small. Serious adverse events were reported in the placebo arm in 18 trials (34%) and in the surgical arm in 22 trials (41.5%); in four trials authors did not specify in which arm the events occurred. However, in many studies adverse events were unrelated to the intervention or associated with the severity of the condition. The existing placebo controlled trials investigated only less invasive procedures that did not involve laparotomy, thoracotomy, craniotomy, or extensive tissue dissection. CONCLUSIONS: Placebo controlled trial is a powerful, feasible way of showing the efficacy of surgical procedures. The risks of adverse effects associated with the placebo are small. In half of the studies, the results provide evidence against continued use of the investigated surgical procedures. Without well designed placebo controlled trials of surgery, ineffective treatment may continue unchallenged.